2009
DOI: 10.1007/s11274-009-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Influences of protectants, rehydration media and storage on the viability of freeze-dried Oenococcus oeni for malolactic fermentation

Abstract: Malolactic fermentation (MLF) is an important process in wine production. To achieve successful MLF, expanding interest in ready-to-use Oenococcus oeni starter cultures has placed greater emphasis on developing starter production and preservation methods. In this study, influences of protectants, rehydration media and storage on the viability of O. oeni H-5 when subjected to freeze-drying were investigated. It was found that sodium glutamate (2.5%) was the best protectant, giving the cell viability 72.4%. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…2001; Carvalho et al. 2004; Zhao and Zhang 2005, 2009). In fact, rehydration is a critical step in the recovery of dried micro‐organisms, because cells that were previously subjected to a sublethal injury may not be able to repair in inappropriate rehydration conditions (Costa et al.…”
Section: Spray‐drying Of Micro‐organismsmentioning
confidence: 99%
“…2001; Carvalho et al. 2004; Zhao and Zhang 2005, 2009). In fact, rehydration is a critical step in the recovery of dried micro‐organisms, because cells that were previously subjected to a sublethal injury may not be able to repair in inappropriate rehydration conditions (Costa et al.…”
Section: Spray‐drying Of Micro‐organismsmentioning
confidence: 99%
“…). A possible explanation was the difference in the water‐binding capacity and prevention of cellular ice crystal formation of each saccharide and polyol (Zhao and Zhang ). Among the antioxidants, sodium glutamate and ascorbic acid played important roles in protecting freeze‐dried micro‐organisms (Berny and Hennebert ; Costa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Viable yeast counts were determined prior to freezing ( N 0 ) and after freeze‐drying ( N f ) and were expressed as colony forming units per millilitre (CFU ml −1 ) according to the method of Zhao and Zhang (). Before freezing, suitable dilutions of yeast samples were spread on the surface of the NYDA plate.…”
Section: Methodsmentioning
confidence: 99%
“…The same result was confirmed from our study. However, Zhao et al (2009) found that when add of sodium glutamate was 2.5% (W/V), the survival rate of Oenococcus oeni reach high at 72.4%. The reason may be due to individual differences of strains.…”
Section: Microorganism and Media B Bifidum Bb01 Was From School Of mentioning
confidence: 97%